Comparative analysis for five fixations of Pauwels-I by the biomechanical finite-element method. Issue 5 (27th May 2020) - Jian-Qiao Peng, Matthew; Chen, Hai-Yan; Ju, XiangYang; Hu, Yong; Ayoub, Ashraf; Khambay, Balvinder; Liu, ZiQing; Bai, Bo
Abstract: Background: Little is known about how biomechanics govern the five fixtures such as DHS, MLS, DHS + LS, LP, and HA are accepted as common therapeutic techniques. Aims and objectives: A series of numerical models for a femoral neck fracture of Pauwels-I will be constructed by innovative approach of finite element in order to determine the most optimized option in comparison with biomechanical performance. Method: Twenty sets of computer tomography scanned femora were imported onto Mimics to extract 3 D models; these specimens were transferred to Geomagic-Studio for a simulative osteotomy and kyrtograph; then, they underwent UG to fit simulative solid models; 5 sorts of fixture were then expressed by Pro-Engineer virtually. After processing with HyperMesh, all compartments (fracture model + internal implant) were assembled onto 5 systems: "Dynamic Hip Screw (DHS), Multiple Lag screw (MLS), DHS + LS, femoral Locking Plate (LP) and HemiArthroplasty (HA)." Eventually, numerical models of the finite-elemental analysis were exported to AnSys to determine the solution. Result: Four models of fixation and a simulation of HA for Pauwels-I were established, validated, and analyzed with the following findings: In term of displacement, these 5 fixtures ranged between 0.3801 and 0.7536 mm have no significant difference; in term of stress, the averages of peaks for integral assemblage are b(MLS) = 43.5766 ≈< d(LP) = 43.6657 ≈< e(Ha) = 43.6657 < c(DHS + LS) = 66.5494 < a(DHS) = 105.617 in MPa indicate that MLS, LP and HA are not significantly different, but less than DHS + LS or DHS in each. Conclusion : A fixture of MLS or LP with optional HA should be recommended to clinically optimize a Pauwels-I facture.